A secure energy-efficient routing protocol for WSN - Pathan, Al-Sakib Khan; Hong, Choong Seon (Springer-Verlag, 2007)
The intent of this paper is to propose an energy-efficient routing protocol with data transmission security for wireless sensor networks. We create an energy and distance aware sink-rooted tree in the network which is used for secure data transmissions from the source sensors to the base station. We mainly focus on ensuring authenticity and confidentiality of the sensor reports by adopting one-way hash chain and pre-loaded shared secret keys. To achieve data freshness, there is an optional key refreshment mechanism in our protocol. Along with the detailed description of our protocol, we present an analysis and performance evaluation of our proposal.